Về một cách tiếp cận cơ sở dữ liệu thiếu thông tin - Hùng, Trương Đức; Vương, Lê Tiến (Journal of Computer Science and Cybernetics, 2016)
This paper describes one approach to the problem of extended relational datebase. Fuzzy data can be included in the system at two levels. The first level considers the possibility of making fuzzy queries to the classic relational database. The second level is related to the problem of adding fuzzy information to the system. The evalution function t and the threshold d are introduced for handling and ordering the fuzzy information. On the extended domain of attribute we define different comparison operations are extended to the fuzzy relational database.